PENGARUH DIKLAT DAN BUDAYA ORGANISASI TERHADAP KINERJA MELALUI MOTIVASI PEGAWAI KECAMATAN PANGGUNGREJO KOTA PASURUAN - Mukaffi Khilmi; Woro Utari; Muninghar (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The purpose of this research is to describe the training conditions, organizational culture, motivation and performance of employees in Panggungrejo District, Pasuruan City. To test and analyze the effect of training and organizational culture on employee motivation. To test and analyze the direct effect of training, organizational culture and motivation on employee performance. To test and analyze the indirect effect of training and organizational culture on performance through the motivation of employees of the Panggungrejo District, Pasuruan City. This type of research is explanatory research. This study uses a quantitative approach. The population in this study were employees of the Panggungrejo District Office, Pasuruan City, totaling 44 people. As for the sample in this study amounted to 44 people. The research sampling technique was carried out using a saturated sample. Data analysis was performed by path analysis using the Partial Least Square (PLS) technique using SmartPLS software. The results of the study can be concluded that Performance, Training, Organizational Culture in the Panggungrejo District Office, Pasuruan City are in the very high category while work motivation is in the high category. Training has a significant effect on employee motivation. Organizational culture has a significant effect on employee motivation. Training directly has a significant effect on employee performance. Organizational Culture has no direct significant effect on Employee Performance. Work motivation directly has a significant effect on employee performance. Training indirectly has a significant effect on performance through employee motivation. Training indirectly has a significant effect on performance through employee motivation.